Mitochondrial dynamics and cancer. Issue 5 (May 2017) - Maycotte, Paola; Marín-Hernández, Alvaro; Goyri-Aguirre, Miriam; Anaya-Ruiz, Maricruz; Reyes-Leyva, Julio; Cortés-Hernández, Paulina
Cancer is among the leading causes of death worldwide, and the number of new cases continues to rise. Despite recent advances in diagnosis and therapeutic strategies, millions of cancer-related deaths occur, indicating the need for better therapies and diagnostic strategies. Mitochondria and metabolic alterations have been recognized as important for cancer progression. However, a more precise understanding of how to manipulate mitochondria-related processes for cancer therapy remains to be established. Mitochondria are highly dynamic organelles which continually fuse and divide in response to diverse stimuli. Participation in the aforementioned processes requires a precise regulation at many levels that allows the cell to couple mitochondrial activity to nutrient availability, biosynthetic demands, proliferation rates, and external stimuli. The many functions of these organelles are intimately linked to their morphology. Recent evidence suggests an important link between mitochondrial morphology and disease, including neurodegenerative, inflammatory diseases and cancer. Here, we review recent advances in the understanding of mitochondrial dynamics with a special focus on its relationship to tumor progression.